Pengaruh Kompetensi Kepribadian dan Penyesuaian Diri Akademik Terhadap Hasil Belajar Mahasiswa Calon Guru Bimbingan dan Konseling - Gabriel Daniel Wiguna; Mikhael Udam; Ahmad Sofyan (Universitas Cenderawasih, 2022)
This research aimed to determine the influence of personality competence and academic adjustment on student learning outcome. For the research method, the present research applied quantitative research. The research population involved 101 students of the Guidance and Counseling Study Program of the Faculty of Teacher Training and Education, Cenderawasih University batch 2018, 2019, 2020 and 2021. The results of the study found the influence of personality competence and academic adjustment on student learning outcome where the results of hypothesis testing simultaneously obtained an F-count value of 23.478, F-table 3.09 and a significance value (Sig.) .000 <0.05. Thus, it was concluded that H0Â was rejected and H3Â was accepted, which meant that the variables of personality competence (X1) and academic adjustment (X2) had a simultaneous influence on student learning outcome (Y). In addition, based on the output value of the summary model, the R Square value was 0.324, which meant that the influence of the variables X1 and X2 simultaneously on Y was 32.4% while the 67.6% was determined by other variables that were not examined in this research